Pengaruh Strategi Inovasi terhadap Kinerja Perusahaan E-Commerce Yang Dimoderasi Leadership - Nurabiah; Herlina Pusparini; Nur Fitriyah (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
The innovation strategy is very attached to e-commerce companies which always need innovations with high knowledge and information technology and leadership that has innovations so as to produce good company performance. The purpose of this research is to examine the influence of innovation strategy on company performance mediated by leadership. The type of research used is associative research with a quantitative approach. The sampling technique used purposive sampling method. The sample in this study were e-commerce companies listed on the Indonesia Stock Exchange (IDX) with a total sample of 15 companies and a total of 75 observations. To test the hypothesis used multiple regression analysis using Stata 14.2 application. It can be concluded, among other things, that the value of a company's innovation strategy has no effect on company performance, both accounting performance and market performance, and leadership is not able to moderate/strengthen the relationship between the value of innovation strategy and company performance.